-9x - 2 = x + 1

First we gather like terms.

-9x - 2 - x + 2 = x + 1 - x + 2

-9x - x = 1 + 2

Now, we simplify.

-10x = 3

Now, we isolate x by dividing by -10.

-10x / -10 = 3 / -10

x = -0.3

Check:

-9(-0.3) - 2 = -0.3 + 1

2.7 - 2 = 0.7

0.7 = 0.7

Therefore, x = -0.3

To solve this, we have to isolate the x so we can find the x value. We first move the variables to one side to solve this:

-2=10x+1

Then we move the 1 to the left side by subtracting it from both sides.

-3=10x.

Now you divide 10 on both sides. When you divide it on the right side, the 10's cancel out so you are left with dividing the -3/10. You get -0.3.

x= -0.3. We can check this by substituting x into the original equation:

-9(-0.3)-2= -0.3+1

2.7-2=0.7

0.7=0.7. Both sides give the same answers. So, the x value of -0.3 is correct.